Analisa Peran Pengawas Minum Obat (PMO) Dalam Mendampingi Pasien Tuberkulosis di Kota Kupang - Fiane de Fretes; Yuslince Elisalonika Mangma; Dennys Christovel Dese (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Kupang City ranks first out of 22 districts/cities with TB cases. Most cases were in 2017, namely 767 cases, while in 2018 cases were decresing to 645 cases. Although data shows a decrease in the number of cases, the success rate of TB in Kupang City in the last two years (85% in 2017 and 81% in 2018) has not yet reached the target of the NTT Provincial Health Office Strategic Plan, which is 90%. TB patients in NTT have PMO availability of 63.3%, this shows that PMO availability is in the quite good category. However, Riskesdas data shows that TB patients in NTT still do not take medication regularly and there is a problem with withdrawal. Purpose: The purpose of this study was to describe the role of supervisors taking medication for tuberculosis patients. Methods: This study uses descriptive qualitative methods. The type of data collected in this study is primary data. The study was conducted on six participants for the data collection process. The participants were five PMOs and one nurse as data triangulation. Results: From the results of this study, it was found the role of PMO in assisting TB patients with the theory of holistic care by Madeleine Leininger, namely: knowledge of PMO; the role of PMO as a companion for TB patients; the role of PMO in preventing transmission and treatment of TB patients; the role of PMO utilizing of health insurance; the role of PMOs in pursuing alternative medicine; the PMO's role in engaging with others to provide support; the role of the PMO in seeking spiritual support; the role of the PMO in finding reliable information sources; the role of health workers in facilitating OAT availability; the role of PMO in utilizing technology. Conclusion: PMO cannot do its job optimally if PMO has few knowledges of TB disease. On the other hand, if the PMO has plenty knowledge of TB disease, PMO will perform its role optimally.